2019
DOI: 10.1108/oir-09-2018-0279
|View full text |Cite
|
Sign up to set email alerts
|

@Houstonpolice: an exploratory case of Twitter during Hurricane Harvey

Abstract: Purpose The purpose of this paper is to examine the Houston Police Department (HPD)’s public engagement efforts using Twitter during Hurricane Harvey, which was a large-scale urban crisis event. Design/methodology/approach This study harvested a corpus of over 13,000 tweets using Twitter’s streaming API, across three phases of the Hurricane Harvey event: preparedness, response and recovery. Both text and social network analysis (SNA) techniques were employed including word clouds, n-gram analysis and eigenve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“… Reicher and Stott [ 16 ] COVID-19 Considers the impact of the COVID-19 outbreak on collective disorder. Yang and Stewart [ 17 ] Hurricane Studies police use of the social media platform, Twitter, by the Houston Police Department during Hurricane Harvey and recommends a three-phase strategy for emergency responders that publicly communicates their preparedness, response and recovery efforts. …”
Section: Police-community Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“… Reicher and Stott [ 16 ] COVID-19 Considers the impact of the COVID-19 outbreak on collective disorder. Yang and Stewart [ 17 ] Hurricane Studies police use of the social media platform, Twitter, by the Houston Police Department during Hurricane Harvey and recommends a three-phase strategy for emergency responders that publicly communicates their preparedness, response and recovery efforts. …”
Section: Police-community Relationsmentioning
confidence: 99%
“…In many instances, these accounts were meant to reply to citizen requests, tackle misinformation, and push correct information forward [ 12 ]. Yang and Stewart [ 17 ]; however, found that Twitter use by police departments, and other first responders, largely focused on protocol, reassurance and community resilience. This discrepancy is echoed by Hughes, St. Denis, Palen, and Anderson [ 15 ] who stress that online communication practices differ across departments and across media types and no standardised procedures are available.…”
Section: Police-community Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another stream of research is performed to investigate the use of social media by the authorities and officials during crisis and emergency, particularly examining social media contents based on the stages of crisis (e.g. Yang and Stewart, 2019; Xu, 2020). Yang and Stewart (2019) investigated the Houston Police Department's public engagement using Twitter during Hurricane Harvey crisis and revealed that governmental agencies' accounts take an influential role during emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Stewart, 2019; Xu, 2020). Yang and Stewart (2019) investigated the Houston Police Department's public engagement using Twitter during Hurricane Harvey crisis and revealed that governmental agencies' accounts take an influential role during emergencies. Their investigation was done across three phases of the disaster, including preparedness, response, and recovery.…”
Section: Introductionmentioning
confidence: 99%